Dipyridamole Inhibits Platelet Aggregation in Whole Blood - Gresele, P; Zoja, C; Deckmyn, H; Arnout, J; Vermylen, J; Verstraete, M (Thrombosis and Haemostasis, 1983)
Dipyridamole possesses antithrombotic properties in the animal and in man but it does not inhibit platelet aggregation in plasma. We evaluated the effect of dipyridamole ex vivo and in vitro on platelet aggregation induced by collagen and adenosine- 5’-diphosphate (ADP) in human whole blood with an impedance aggregometer. Two hundred mg dipyridamole induced a significant inhibition of both ADP- and collagen-induced aggregation in human blood samples taken 2 hr after oral drug intake. Administration of the drug for four days, 400 mg/day, further increased the antiplatelet effect. A significant negative correlation was found between collagen-induced platelet aggregation in whole blood and dipyridamole levels in plasma (p <0.001). A statistically significant inhibition of both collagen (p <0.0025) and ADP-induced (p <0.005) platelet aggregation was also obtained by incubating whole blood in vitro for 2 min at 37° C with dipyridamole (3.9 μM). No such effects were seen in platelet-rich plasma, even after enrichment with leukocytes. Low-dose adenosine enhanced in vitro inhibition in whole blood.Our results demonstrate that dipyridamole impedes platelet aggregation in whole blood by an interaction with red blood cells, probably involving adenosine.
Keywords: Adenosine; Dipyridamole; Impedance aggregometry; Platelet aggregation; Red blood cells; Whole blood